Enthalpy-entropy compensation analysis of the triclocarban dissolution process in some {1,4-dioxane (1)?+?water (2)} mixtures (2023)
The equilibrium solubility of triclocarban in {1,4-dioxane (1) + water (2)} mixtures at 293.15 K to 313.15 K was reported. Mole fraction solubility increases continuously from neat water to neat 1,4-dioxane at all temperatures. Solubility behavior was adequately correlated by means of a number of cosolvency models including the Jouyban-Acree model. Based on the Gibbs and van't Hoff equations the respective apparent thermodynamic quantities of dissolution were calculated. Non-linear enthalpy-entropy compensation analysis is observed indicating different dissolution mechanism with the variation in mixtures composition. © 2018 Elsevier B.V.